Ser un cuerpo o tener un cuerpo, ¿cuál es la cuestión? Reflexiones psicoanalíticas acerca del cuerpo en el mundo científico y capitalista (2019)
The article points out an important difference established between being a body and having a body from the psychoanalytic view. The latter, to specify that in humans the way that language is echoed in the body through grammatical devices of the drive, is essential. Similarly, a distinction arises to point out that when we speak of human beings we mean anything in relation to the drives, then unlike the instinctive, that is due more to the order of behavior and patterns of animal character already installed. This article concludes with a look that sets today science and capitalism concerning the bodies.